Fatty Acid and Associated Gene Expression Analyses of Three Tree Peony Species Reveal Key Genes for α-Linolenic Acid Synthesis in Seeds - Zhang, Qing-Yu; Yu, Rui; Xie, Li-Hang; Rahman, Md Mahbubur; Kilaru, Aruna; Niu, Li-Xin; Zhang, Yan-Long (Frontiers in Plant Science, 2018)
The increasing demand for healthy edible oil has generated the need to identify promising oil crops. Tree peony (Paeonia section Moutan DC.) is a woody oil crop with α-linolenic acid contributing for 45% of the total fatty acid (FA) content in seeds. Molecular and genetic differences that contribute to varied FA content and composition among the wild peony species are however, poorly understood. Analyses of FA content and composition during seed development in three tree peony species (P. rockii, P. potaninii, and P. lutea) showed varied FA content in the three species with highest in P. rockii, followed by P. potaninii, and P. lutea. Total FA content increased with seed development and reached its maximum in its final stage. Seed FA composition analysis of the three species also revealed that α-linolenic acid (C18:3) was the most abundant, followed by oleic (C18:1) and linoleic (C18:2) acids. Additionally, quantitative real-time RT-PCR analyses of 10 key seed oil synthesis genes in the three tree peony species revealed that FAD3, FAD2, β-PDHC, LPAAT and Oleosin gene expression levels positively correlate with total FA content and rate of accumulation. Specifically, the abundance of FAD3 transcripts in P. rockii compared with P. potaninii, and P. lutea suggests that FAD3 might play in an important role in synthesis of α-linolenic acid via phosphatidylcholine-derived pathway. Overall, comparative analyses of FA content and composition in three different peony species revealed correlation between efficient lipid accumulation and lipid gene expression during seed development. Further characterization and manipulation of these key genes from peonies will allow for subsequent improvement of tree peony oil quality and production.